2017
DOI: 10.1097/ico.0000000000001270
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rate and Graft Stability With Fibrin Glue Compared With Suture and Autologous Blood Coagulum for Conjunctival Autograft Adherence in Pterygium Surgery: A Meta-Analysis

Abstract: This meta-analysis reveals the superiority of FG over sutures as the use of FG can significantly reduce the recurrence rate, but no significant difference in graft stability was found between FG and sutures. No significant difference was found in the recurrence rate between FG and ABC, but graft stability was found to be better with FG compared with ABC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
2
10
0
2
Order By: Relevance
“…It has been suggested that immediate adherence of the graft may inhibit fibroblast ingrowth and reduce recurrence. 33 Based on our study, we found that mild graft retraction and dehiscence, such as GS of grade 1 or 2, do not affect recurrence but are essential for wound healing. However, serious dehiscence (grade 3) and even dislocation (grade 4) may directly lead to recurrence, which necessitates repeated surgery to attach the graft as soon as possible.…”
Section: Discussionmentioning
confidence: 62%
“…It has been suggested that immediate adherence of the graft may inhibit fibroblast ingrowth and reduce recurrence. 33 Based on our study, we found that mild graft retraction and dehiscence, such as GS of grade 1 or 2, do not affect recurrence but are essential for wound healing. However, serious dehiscence (grade 3) and even dislocation (grade 4) may directly lead to recurrence, which necessitates repeated surgery to attach the graft as soon as possible.…”
Section: Discussionmentioning
confidence: 62%
“…However, this technique also presents drawbacks: intraoperatively takes more time, and postoperatively presents a high rate of graft loss. Maiti et al 14 showed no significant difference in the pterygium recurrence rate between conjunctival autograft fixation with fibrin glue vs. autologous blood coagulum, but graft stability was found to be better with the former.…”
Section: Discussionmentioning
confidence: 98%
“…Além disso, inúmeros pacientes relataram ausência das complicações relacionadas com suturas, como sensação de corpo estranho (13) . Porém, vale ressaltar, que alguns estudos alertam sobre resultados conflitantes com estabilidade e recorrência da doença após o uso desse material (14) .…”
Section: Discussionunclassified
“…Os resultados apresentados corroboram com, Maiti et al (14) ao apontar que apesar do número reduzido de casos de recorrência entre os pacientes, que foi utilizado o adesivo de fibrina, não houve diferença estatística significativa entre os grupos.…”
Section: Autorunclassified